Gambaran Program Bimbingan Pribadi dan Sosial untuk Meningkatkan Penyesuaian Sosial Siswa - Harahap, Ade Chita Putri; Siregar, Dewi Kumala Kholisa; Husna, Natasya; Putri, Maulida Amelia; Batubara, Muhammad Alwi; Ritonga, Rizki Rahmayani; Supriyadi, Supriyadi; Ramadhita, Zahrani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to get an overview of the personal and social guidance program in improving students' social adjustment in the school environment. The researcher used a qualitative method to understand the overview of the guidance program. The data collection technique used was interviews. The interview subject was the Guidance Counselor from MA Mualimin UNIVA, Medan City. The results show that the methods used in personal and social guidance to improve students' social adjustment are group and individual guidance. The materials used in the guidance program include effective communication skills, emotional management abilities, building self-confidence, coping with stress, and understanding the importance of maintaining mental and physical health. However, the researcher also found obstacles in the implementation of the personal and social guidance program, such as lack of support from students' parents, time constraints, and resources. Therefore, research on efforts to improve students' social adjustment is very important. Some previous studies have shown that group guidance programs can help students improve their social adjustment. Through effective personal and social guidance programs, students can learn to recognize and address personal or social problems that affect their ability to adapt to their environment.